Penegakan Hukum Administrasi Dalam Pelanggaran Pemilihan Umum Ditinjau Dari Undang-Undang Nomor 7 Tahun 2017 - Rumbia, Dedi; Nirahua, Salmon Eliazer Marthen; Piris, Hendry John (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Election administration violations include violations of any procedures, procedures or mechanisms related to the implementation of election administration at every stage of the election administration, the resolution of which is the responsibility of the Bawaslu which accepts, investigates, assesses, and decides on election administration violations.Purposes of the Research: This study aims to identify and analyze election violations in terms of Law Number 7 of 2017. And enforcement of administrative law against election violations in terms of Law Number 7 of 2017.Methods of the Research: This study uses normative legal research, legal approaches and conceptual approaches using data sources in the form of primary, secondary and tertiary legal materials. The legal material analysis technique used in this work is qualitative in nature, meaning that the collected data must be separated according to its category and then interpreted to obtain research answers.Results of the Research: The results of the study show that the administrative sanctions imposed on the perpetrators of election violations do not have a deterrent effect, because the sanctions imposed only improve procedures, procedures and mechanisms at the stage of summing up the election results. The sanctions imposed cause the person or several people to repeat the same mistake.